2018
DOI: 10.1088/1361-6463/aa9f55
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic-resonance-induced spin pumping in Co20Fe60B20/Pt systems: damping investigation

Abstract: Microstrip line ferromagnetic resonance (MS-FMR) has been used to investigate the dependence of the magnetic damping enhancement on the thickness of Co20Fe60B20 and Pt due to spin pumping. Samples with variable thicknesses of Co20Fe60B20 (Pt) are used to determine the spin mixing conductance (spin diffusion length) via the thickness dependence of the Gilbert damping parameter α of Co20Fe60B20/Pt heterostructures. The results obtained from the analysis of the MS-FMR measurements reveal that α increases linearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The effect of including a thickness-dependent λ sf in the analysis is shown in Table I. Fitting with a constant λ sf gives values typical of previous FMR analyses between 1 and 2 nm [13,18], but here, the inclusion of a NM layer thickness dependence gives bulk λ sf close to 10 nm, as reported elsewhere [24,29,60]; this resolves the discrepancy between values of λ sf from different methods. The magnitude of for Pt supports reports that the EY mechanism is the dominant source of spin-flip scattering [41] and is of a similar order of magnitude (10 −1 ) to reported values [2].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The effect of including a thickness-dependent λ sf in the analysis is shown in Table I. Fitting with a constant λ sf gives values typical of previous FMR analyses between 1 and 2 nm [13,18], but here, the inclusion of a NM layer thickness dependence gives bulk λ sf close to 10 nm, as reported elsewhere [24,29,60]; this resolves the discrepancy between values of λ sf from different methods. The magnitude of for Pt supports reports that the EY mechanism is the dominant source of spin-flip scattering [41] and is of a similar order of magnitude (10 −1 ) to reported values [2].…”
Section: Resultssupporting
confidence: 66%
“…The transport properties of such systems have been probed with several techniques, including magnetoresistance [5,9,10], magnetooptics [11], spin Hall angle [12][13][14], ferromagnetic resonance (FMR) [15][16][17][18][19][20], and combinations of these techniques [6,[21][22][23]. A range of values for the spin-diffusion length λ sf have been reported for Pt at room temperature from 1.2 nm up to 11 nm [11,13] from these different methods, with FMR measurements giving lower values for λ sf than spin Hall measurements [13,18,24,25 The physical basis of the interfacial contribution is ascribed to additional spin-flip scattering associated with an effective interface thickness due to disorder [6], however, it was shown theoretically for an atomically flat FM/heavy metal interface that d-d hybridization enhances the damping [26], which effectively increases g ↑↓ eff . Furthermore, the influence on spin pumping and the spin-mixing conductance of crystallographic structuring at the interface has recently been demonstrated [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…1(a). The choice of Fe rich FeCoB and the aforementioned optimized thicknesses of Pt and FeCoB allow to have sufficient DMI and PMA [50][51][52] suitable to stabilise skyrmions, while limiting spin pumping effects which would otherwise lead to an increased damping coefficient 53 . We estimate by FMR a Gilbert damping constant of α = 0.022 (see Supplementary Figure 1) for our samples which is relatively low for such multilayer systems 53 .…”
Section: Multilayer Compositionmentioning
confidence: 99%
“…The choice of Fe rich FeCoB and the aforementioned optimized thicknesses of Pt and FeCoB allow to have sufficient DMI and PMA [50][51][52] suitable to stabilise skyrmions, while limiting spin pumping effects which would otherwise lead to an increased damping coefficient 53 . We estimate by FMR a Gilbert damping constant of α = 0.022 (see Supplementary Figure 1) for our samples which is relatively low for such multilayer systems 53 . The overall magnetic volume is enhanced with the 20 repetitions of the trilayer, which not only increases the thermal stability of the skyrmions 28 but also provides a larger signalto-noise ratio for inductive measurements.…”
Section: Multilayer Compositionmentioning
confidence: 99%
“…Another concluded that spin memory loss was unaffected by PIM 29 . However a ferromagnetic resonance (FMR) study reported that a reduction in Pt PIM resulted in a decrease in the interfacial contribution to damping 20,30 . The controversy is not limited to transition metal/HM systems, with studies of PIM and spin transport in ferrimagnetic YIG/Pt reporting that PIM has either no effect, as determined from FMR measurements 31 , or a significant effect, from temperature-dependent spin Hall effect measurements 32 and angular-dependent FMR analysis 33 .…”
mentioning
confidence: 99%